2018
DOI: 10.13109/zptm.2018.64.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Operationalized Psychodynamic Diagnosis System and Outcome of Psychodynamic Inpatient Psychotherapy in Male and Female Patients

Abstract: Objective: To compare male and female patients with regard to the Operationalized Psychodynamic Diagnosis (OPD-2) system, treatment variables, and outcome after multimodal psychodynamic inpatient psychotherapy. Methods: At the beginning and at the end of inpatient treatment in a multimodal psychodynamic setting, patients were examined with the OPD-2 system as well as with three self-assessment questionnaires addressing interpersonal problems (Inventory of Interpersonal Problems, IIP), and psychopathology: Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…In terms of the association of therapy satisfaction with participants’ gender, the results of previous studies have varied, and no consistent conclusions have been reached ( 59 ). For example, both Vitinius et al ( 59 ) and Schneider and Heuft’s ( 70 ) studies found that client gender did not have a significant impact on psychotherapy success. Although our analysis implied that male participants were more satisfied with psychotherapy than female participants, more research is strongly suggested to clarify the potential factors and mechanisms contributing to this gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the association of therapy satisfaction with participants’ gender, the results of previous studies have varied, and no consistent conclusions have been reached ( 59 ). For example, both Vitinius et al ( 59 ) and Schneider and Heuft’s ( 70 ) studies found that client gender did not have a significant impact on psychotherapy success. Although our analysis implied that male participants were more satisfied with psychotherapy than female participants, more research is strongly suggested to clarify the potential factors and mechanisms contributing to this gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy discontinuation rates were low and did not differ between the sexes. Overall, both sexes seem to benefit equally from psychodynamic inpatient psychotherapy in terms of symptom improvement [ 22 ].…”
Section: Personality Functioning In Psychiatrymentioning
confidence: 99%
“…Nesses estudos, em sua maioria, o OPD foi aplicado por avaliadores que receberam treinamento específico para o manejo do instrumento e as investigações foram conduzidas de forma a avaliar a confiabilidade e validade do uso do instrumento na avaliação de pacientes submetidos a tratamento psicoterápico (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Issn 2318-0404iunclassified
“…Os resultados obtidos por esses estudos consideraram o OPD como um instrumento adequado quando utilizado para avaliar os processos de tratamento recebido, tendo amplo uso dentro da saúde mental. Para esses estudos o mesmo atenderia as demandas de proposta de pesquisa e seria um instrumento confiável para uso em contextos de avaliação clínica (13)(14)(15)(16)(17) . Observou-se que dentre esses estudos publicados, parte deles utilizaram entrevistas gravadas como método de coleta dos dados para preenchimento do OPD, sendo que em alguns deles, essas entrevistas não foram conduzidas levando em consideração pontos específicos avaliados pelo protocolo.…”
Section: Issn 2318-0404iunclassified